PROFILE OF WOMEN WITH LEG ULCERS DUE TO SICKLE CELL DISEASE (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: to characterize the profile of women with leg ulcers resulting from sickle cell disease treated at a public health institution in Brazil. Method: historical cohort study conducted in the outpatient sector with a sample of women with sickle cell disease and leg ulcer, followed from 1998 to 2014. The data were extracted from the medical record and included sociodemographic, clinical and ulcer-related variables, and underwent descriptive statistical analysis. Results: of the 17 women, 64.7% were cured, 58.8% were aged between 30 and 39 years, 64.7% declared themselves brown, 70.6% were without partners, 41.2% had incomplete elementary education, 52, 9% had an income of 2 to 3 minimum wages, 70.6% were eutrophic and 82.4% used vitamin supplements. Women had a total of 29 ulcers, 52.9% had a single ulcer, 41.4% were located in the malleolar region, 55.17% were between 2 and 36 months, all classified as stage 3. The treatment was with coverings and Unna’s boot. Conclusion: the women received care from specialist nurses and most were cured with up to eight months of follow-up, which required a nursing consultation, including clinical evaluation, topical treatment and application of compression therapy.